2011
DOI: 10.1590/s1516-35982011000400009
|View full text |Cite
|
Sign up to set email alerts
|

Modelos de regressão aleatória para descrição da curva de crescimento de codornas de corte

Abstract: RESUMO -Objetivou-se com este trabalho comparar diferentes modelos de regressão aleatória, ajustados por meio de funções polinomiais de Legendre de diferentes ordens, para avaliar o que melhor se ajusta ao estudo genético da curva de crescimento de codornas de corte. Os dados utilizados são provenientes de 26.835 e 27.447 observações, de 3.909 e 4.040 codornas de corte das linhagens UFV-1 e UFV-2. O peso corporal nas duas linhagens foi avaliado aos 1, 7, 14, 21, 28, 35 e 42 dias de idade. Ordens de ajuste das … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
4
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
6
4
1
3
Order By: Relevance
“…The highest genetic correlation (0.972) was observed between 21 and 28 days of age, suggesting that selection at 28 days of age can be effective, considering that correlation between 28 and 35 days of age (selection age) was also high (0.965). These results are consistent with those reported by Dionello et al (2008) and Bonafé et al (2011), who also reported high genetic correlation from 7 days of age. The permanent environmental correlations were, in general, similar to the genetic correlations, which highlights the importance of strong permanent effect on body weight, indicating that environmental factors may influence body weight at all ages.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The highest genetic correlation (0.972) was observed between 21 and 28 days of age, suggesting that selection at 28 days of age can be effective, considering that correlation between 28 and 35 days of age (selection age) was also high (0.965). These results are consistent with those reported by Dionello et al (2008) and Bonafé et al (2011), who also reported high genetic correlation from 7 days of age. The permanent environmental correlations were, in general, similar to the genetic correlations, which highlights the importance of strong permanent effect on body weight, indicating that environmental factors may influence body weight at all ages.…”
Section: Resultssupporting
confidence: 93%
“…However, animal permanent environmental variance displayed lower values (Figure 1). Similar results were reported by Akbas et al (2004), Dionello et al (2008) and Bonafé et al (2011), while studying meat quails, in which both variances also increased with age.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Segundo BONAFÉ et al (2011a), modelos de regressão aleatória permitem a obtenção de diferentes curvas de valores genéticos associadas aos diferentes indivíduos e consideram as mudanças nas variâncias genéticas e residuais, ao longo do tempo.…”
Section: Introductionunclassified